Big data, small concepts: histosophy as an approach to longue-durée history. (2nd January 2021) - de Miranda, Luis; Chabal, Emile
ABSTRACT: In this essay, we sketch out a method, histosophy, which makes possible the study of intellectual history and conceptual genealogy both in depth and over long periods of time. Histosophy uses digital tools to survey 'large issues within small compasses.' A genealogy of signifiers, it considers metonymic parts of a problem in order to contribute precisely and coherently to a larger perspective. We outline the theoretical contours of our approach. We exemplify how it works in practice by looking at the signifier 'esprit de corps', the study of which is presented in detail in the histosophical book The Genealogy of Esprit de Corps (Edinburgh University Press, 2019). The phrase 'esprit de corps' has been widely used since the eighteenth century in different discourses (political, military, sociological, etc.), but it is sufficiently limited that its genealogy can be traced across centuries and nations with precision, coherence, clarity, and with the help of automated search engines. By contrast, related but bigger concepts like freedom, individualism or solidarity are part of dozens of disparate and fuzzy discourses, so often uttered that the analysis of modern uses is problematic. The histosophical methodology is applicable in six discrete stages, here outlined.